The endocannabinoid system in appetite regulation and treatment of obesity - Marija Kurtov; Igor Rubinić; Robert Likić (Wiley, 2024)
Abstract The endocannabinoid system (ECS) is a complex cell‐signaling system that is responsible for maintaining homeostasis by modulating various regulatory reactions in response to internal and environmental changes. The influence of ECS on appetite regulation has been a subject of much recent research, however, the full extent of its impact remains unknown. Current evidence links human obesity to ECS activation, increased endocannabinoid levels in both central and peripheral tissues, along with cannabinoid receptor type 1 (CBR1) up‐regulation. These findings imply the potential pharmacological use of the ECS in the treatment of obesity. Here, we present various pathophysiological processes in obesity involving the ECS, highlighting different pharmacological options for modulating endocannabinoid activity to treat obesity. However, the potential of those pharmacological possibilities remains under investigation and requires further research.